2018
DOI: 10.14814/phy2.13684
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of high-intensity intermittent training and vitamin D supplementation on glycemic control in overweight and obese adults

Abstract: High‐intensity intermittent training (HIIT) has been shown to reduce the risk of chronic conditions including the development of type 2 diabetes mellitus (T2DM). Independently, a low vitamin D status has also been linked to the prevalence of T2DM. The aim of this study was to investigate if there was a synergistic metabolic effect of HIIT and vitamin D supplementation on glycemic control. A total of 20 male and female participants (age, 34 ± 9 year; BMI, 31.4 ± 2.8 kg·m−2) completed 6 weeks HIIT, and were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…This suggests that a continuous rather than an intermittent type of Nordic Walking training is preferable in inducing the lower limb strength and muscle mass changes in elderly people. Similarly, no relation between the lower limb performance and 25(OH)D concentration has been reported either in the study investigating combined effects of six weeks of HIIT on a cycloergometer and 4000 IU/day Vitamin D supplementation [ 51 ]. However, in the aforementioned study [ 51 ], the participants’ performance increased regardless of the supplementation or placebo intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that a continuous rather than an intermittent type of Nordic Walking training is preferable in inducing the lower limb strength and muscle mass changes in elderly people. Similarly, no relation between the lower limb performance and 25(OH)D concentration has been reported either in the study investigating combined effects of six weeks of HIIT on a cycloergometer and 4000 IU/day Vitamin D supplementation [ 51 ]. However, in the aforementioned study [ 51 ], the participants’ performance increased regardless of the supplementation or placebo intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, no relation between the lower limb performance and 25(OH)D concentration has been reported either in the study investigating combined effects of six weeks of HIIT on a cycloergometer and 4000 IU/day Vitamin D supplementation [ 51 ]. However, in the aforementioned study [ 51 ], the participants’ performance increased regardless of the supplementation or placebo intervention. The lack of effect on the lower limb in the HI-NW group could be related different specificities of the applied training load (Nordic Walking vs. cycling), testing (peak torque vs peak power output and VO 2 max) as well as differences in participants’ age (19–45 vs. 62–82 years old).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, body fat is significantly negatively correlated with serum 25(OH)D levels [90] and obese individuals have a higher risk of vitamin D deficiency [91,92]. In addition, lipolysis may be impaired in obese individuals [93], and obesity affects the regulation of vitamin D metabolism enzymes [94], which may explain why 25(OH)D levels in overweight and obese adults were not altered in the Lithgow study [48]. Second, exercise in the fed and fasted states differed in terms of energy metabolism substrates.…”
Section: Limitations and Perspectivesmentioning
confidence: 91%
“…Twelve human studies investigated the effect of endurance exercise training on serum 25(OH)D levels and did not yield consistent results (Table 1). Some studies found that chronic endurance exercise training can significantly increase serum 25(OH)D levels [39][40][41][42][43][44][45], but other studies have reported contradicting results [46][47][48][49][50]. However, when we sorted these studies, we found that in people with vitamin D deficiency {25(OH)D < 20 ng/mL or 50 nmol/L [57]}, endurance training can significantly improve serum 25(OH)D levels [39,40,42,43,45], and even severe vitamin D deficiency status (<10 ng/mL) improved to vitamin D deficiency status (10-20 ng/mL) in postmenopausal women [42].…”
Section: The Effect Of Chronic Endurance Exercise Training 221 Human ...mentioning
confidence: 99%
See 1 more Smart Citation